Phenology of the important coleopterous pests of pine forests in the Western Cape, South Africa - Tribe, Geoffrey Darryl (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1992)
The phenology of the three exotic pine bark beetles present in South Africa was determined in the south-western Cape Province. Results from weekly trapping of adult beetles using trap-logs over a period of five years showed that the different species had activity peaks at different times of the year. Hylastes angustatus was the most consistent with 95% of the beetles captured in September and October. The Orthotomicus erosus activity peak was more variable but always occurred in the summer months (October to February) when 84% of the beetles were captured. Hylurgus ligniperda was the most variable, being found in every month of the year, although an autumn peak representing 37% of the beetles occurred in April/May. Activity peaks of each species coincided with distinct climatic conditions. Buried and partially-buried pine logs placed vertically in the soil to simulate roots and stems of seedlings were used to determine the colonisation sites of the three bark beetle species. Ninety-eight percent of O. erosus beetles were found in the protruding parts of the logs while 86% of H. ligniperda beetles were found mainly below soil level. H. angustatus were intermediate, entering the logs at or just below the soil interface but colonising mainly the buried parts in which 64% of the beetles were found. Both H. angustatus and H. ligniperda were able to detect and colonise logs buried horizontally at depths of 400mm, but O. erosus beetles were unable to do so. For adequate protection of seedlings from bark beetles, insecticide should be applied to both stems and roots. The phenology of the indigenous pine needle feeders Oosomus varius (Curculionidae) and Prasoidea sericea (Chrysomelidae) was determined by counting, at weekly intervals, the number of beetles present on 10 young pine trees. The O. varius activity peak occurred in August where 42% of all beetles were active, with 87% of the beetles present in July, August and September. P. sericea also had their activity peak in August when 60% of all beetles were active, but with August and September alone accounting for 87% of the beetles. The occurrence of the activity peaks was consistent each year over the five-year study period. This information facilitates the correct timing of prophylactic insecticide sprays.
Keywords: Beetles -- South Africa; Bark beetles -- South Africa -- Cape of Good Hope; Scolytidae; Phenology -- South Africa; Phenology -- South Africa -- Cape of Good Hope